Growth of Bamboo Lobster (Panulirus versicolor; Latreille, 1804) Fed with Feed Made from Sosodek Fish Meal (Atherinomorus lacunosus) - Muhammad Safir; Intan Sukarmin Maasily; Novalina Serdiati; R Adharyan Islamy (Postgraduate, University of Mataram, 2024)
Bamboo lobster (Panulirus versicolor) is a marine commodity with promising prospects for aquaculture development. Feed is a critical issue in the growth of P. versicolor, necessitating an effective, affordable solution that promotes optimal growth. This study aimed to examine the use of sosodek fish meal (A. lacunasus) as a nutrient source to enhance the growth of P. versicolor. Specimens of P. versicolor (weighing 79.97±38 g) were obtained from local fishermen in Togean District, Tojo Una-Una Regency, Central Sulawesi. The experiment tested the use of sosodek fish meal as a feed ingredient at different percentages: 0% (control), 10% (A), 20% (B), and 30% (C). The lobsters were kept in containers with 25 liters of seawater, with one lobster per container, and each treatment was replicated three times. Feed was given at 5% of body weight, three times daily. Body weight was measured every two weeks. Water quality was maintained within a range suitable for P. versicolor. The results indicated that weight gain and daily growth rates, from highest to lowest, were observed in treatment C (11.84 g and 0.49%/day), B (7.4 g and 0.21%/day), A (2.82 g and 0.09%/day), and control (2.38 g and 0.08%/day). Feed conversion ratios, from lowest to highest, were recorded as C (13.1), B (25.1), A (71.9), and control (64.0). Feed utilization efficiency, from highest to lowest, was seen in treatment C (10.28%), B (4.32%), A (1.85%), and control (1.72%). Survival rates for all treatments were 100%. The analysis showed that individual weight gain, daily growth rates, and feed utilization efficiency were significantly higher, and feed conversion ratios were lower in treatment C (30% sosodek fish meal) compared to other treatments (P<0.05). Utilizing 30% sosodek fish meal as feed ingredient significantly enhances the growth of P. versicolor.